2023
DOI: 10.1371/journal.pone.0282520
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and its drivers: An empirical study of the vaccine hesitant group in Malaysia

Abstract: Background Sporadic outbreaks of COVID-19 remain a threat to public healthcare, especially if vaccination levels do not improve. As Malaysia begins its transition into the endemic phase, it is essential to identify the key determinants of COVID-19 vaccination intention amongst the pockets of the population who are still hesitant. Therefore, focusing on a sample of individuals who did not register for the COVID-19 vaccination, the current study integrated two widely used frameworks in the public health domain—t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…30 These effects can be on the individual level but also on the area level with influence from family, friends, community members or public health policy makers. 33 From a questionnaire study, the most given reasons to refuse vaccine were being against vaccines in general, concerns about safety/thinking that a vaccine produced in a rush is too dangerous, considering the vaccine useless because of the harmless nature of COVID-19 and a general lack of trust. 32…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…30 These effects can be on the individual level but also on the area level with influence from family, friends, community members or public health policy makers. 33 From a questionnaire study, the most given reasons to refuse vaccine were being against vaccines in general, concerns about safety/thinking that a vaccine produced in a rush is too dangerous, considering the vaccine useless because of the harmless nature of COVID-19 and a general lack of trust. 32…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Empirical studies in developed and developing countries have identified several factors influencing the hesitancy, perception and willingness to vaccinate against diseases, such as COVID-19 among others. These factors determining the hesitancy, perception, willingness and decision to vaccinate are gender differences (Vaithilingam et al ., 2023), age (Burke et al ., 2021), educational background (Roy et al ., 2022), family characteristics including household size and the income of the household head (Tan et al ., 2022), sectors and urbanization (Mishi et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%